Conceptual design and simulation study of an autonomous indoor medical waste collection robot - Shaju, Shawn; George, Thomas; Francis, Jithin Kunnath; Joseph, Manu; Thomas, Mervin Joe (IAES International Journal of Robotics and Automation (IJRA), 2023)
Solid waste management is one of the critical challenges seen everywhere, and the coronavirus disease (COVID-19) pandemic has only worsened the problems in the safe disposal of infectious waste. This paper outlines a design for a mobile robot that will intelligently identify, grasp, and collect a group of medical waste items using a six-degree of freedom (DoF) arm, You Only Look Once (YOLO) neural network, and a grasping algorithm. Various designs are generated before running simulations on the selected virtual model using Robot Operating System (ROS) and Gazebo simulator. A lidar sensor is also used to map the robot's surroundings and navigate autonomously. The robot has good scope for waste collection in medical facilities, where it can help create a safer environment.